2014
DOI: 10.1111/cid.12214
|View full text |Cite
|
Sign up to set email alerts
|

Zirconia‐Based Screw‐Retained Prostheses Supported by Implants: A Retrospective Study on Technical Complications and Failures

Abstract: This study shows that zirconia-based implant-supported fixed prostheses exhibit satisfactory treatment outcomes and that screw-retention directly at the implant level is feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 35 publications
2
37
1
Order By: Relevance
“…Indeed, as yet, an assessment of the risk of complete failure has not been reported for implant-supported restorations [32,33]. A retrospective study of zirconia-based screw-retained prostheses supported by implants and including 65 SCs and 91 FDPs was recently made available [34]. The cumulative survival rate was 90.5 % after 5 years.…”
Section: Discussion Survival Estimatesmentioning
confidence: 99%
“…Indeed, as yet, an assessment of the risk of complete failure has not been reported for implant-supported restorations [32,33]. A retrospective study of zirconia-based screw-retained prostheses supported by implants and including 65 SCs and 91 FDPs was recently made available [34]. The cumulative survival rate was 90.5 % after 5 years.…”
Section: Discussion Survival Estimatesmentioning
confidence: 99%
“…Nevertheless, in the clinical reality, a framework is often screwed directly to the implants, avoiding the use of a screw‐retained abutment . This implant‐level (IL) setup is often used in cases due to limited vertical spaces and to reduce costs .…”
Section: Introductionmentioning
confidence: 99%
“…After milling, Y-TZP frameworks have to be veneered with feldspathic or glass ceramics by means of layering, the press or the digital veneering technique 2. However, clinical studies have reported failures such as chipping (cohesive failure of porcelain) and delamination (adhesive failure between the ceramic and framework 3456. Preis et al2 reported that different framework designs, veneer application techniques, and firing regimes influence the number and dimension of failures in zirconia-based all-ceramic crowns.…”
Section: Introductionmentioning
confidence: 99%